2018
DOI: 10.1016/j.cell.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Counteracts β-Lactam Antibiotics by Promoting the Emergence of L-Form Bacteria

Abstract: Summaryβ-lactam antibiotics inhibit bacterial cell wall assembly and, under classical microbiological culture conditions that are generally hypotonic, induce explosive cell death. Here, we show that under more physiological, osmoprotective conditions, for various Gram-positive bacteria, lysis is delayed or abolished, apparently because inhibition of class A penicillin-binding protein leads to a block in autolytic activity. Although these cells still then die by other mechanisms, exogenous lytic enzymes, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 48 publications
(80 reference statements)
8
115
1
Order By: Relevance
“…Intriguingly, Errington and colleagues have recently shown that B. subtilis can enter into the L‐form state when coping stress inside macrophages and that these bacteria retain viability (Kawai et al, ). Host PG degrading enzymes, like lysozyme and PGLYRP2, are proposed to induce emergence of these cell wall deficient intracellular bacteria (Kawai et al, ). Unlike persistent dormant bacteria, L‐forms grow in the presence of beta‐lactam antibiotics and this is much concern to control bacterial infections.…”
Section: Cell Wall Deficiency In Intracellular Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, Errington and colleagues have recently shown that B. subtilis can enter into the L‐form state when coping stress inside macrophages and that these bacteria retain viability (Kawai et al, ). Host PG degrading enzymes, like lysozyme and PGLYRP2, are proposed to induce emergence of these cell wall deficient intracellular bacteria (Kawai et al, ). Unlike persistent dormant bacteria, L‐forms grow in the presence of beta‐lactam antibiotics and this is much concern to control bacterial infections.…”
Section: Cell Wall Deficiency In Intracellular Bacteriamentioning
confidence: 99%
“…Work from decades has accumulated evidence supporting the capacity of many bacteria to switch to a physiological state in which they undergo growth and division in the absence of cell wall (Claessen & Errington, 2019). These cell wall deficient bacteria, known as L-forms, have been extensively studied in Gram-positive bacteria like the intracellular pathogen L. monocytogenes (Studer, Borisova, et al, 2016a;Studer, Staubli, et al, 2016) and Bacillus subtilis (Kawai, Mickiewicz, & Errington, 2018). How this physiological state is represented in the adaptation process to the intracellular lifestyle is currently unknown.…”
Section: Cell Wall Defi Cien C Y In Intr Acellul Ar Bac Teriamentioning
confidence: 99%
“…It was believed previously that the PBP loss of function was directly bactericidal. PBP inactivation by β‐lactams is seen now as the triggering event that initiates more complex, and perhaps even species‐specific, pathways that culminate in bactericidal cell lysis . Perhaps as a consequence (but at the molecular level, for reasons not understood) some resistance mechanisms against the β‐lactams exert a cellular cost.…”
Section: Miraculous Chemistrymentioning
confidence: 99%
“…PBP inactivation by β-lactams is seen now as the triggering event that initiates more complex, and perhaps even species-specific, pathways that culminate in bactericidal cell lysis. [115][116][117][118][119][120] Perhaps as a consequence (but at the molecular level, for reasons not understood) some resistance mechanisms against the β-lactams exert a cellular cost. The notorious Grampositive pathogen S. aureus does not activate its resistance mechanisms until it detects the presence of a β-lactam.…”
Section: Miraculous Chemistrymentioning
confidence: 99%
“…The peptidoglycan layer is also the site of action for antimicrobial agents. Lysozyme, an antimicrobial enzyme critical in animal host defense, is one of the most abundant proteins present on the mucosal surfaces and in body secretions, such as saliva and tears [5, 6]. The epithelial cells secrete lysozyme to protect the host’s mucosal surfaces from infectious bacteria.…”
Section: Introductionmentioning
confidence: 99%